A Network Based Semiotic Analysis: Critical Commentary on the Field and Dynamic Nature of Sense-Making: Theoretical and Methodological Implications - Suerdem, Ahmet (Johannes Kepler Univ, Inst Paedagogik & Psychologie, 2013)
Social representations (SR) are not atomistic entities contained in independent sign units labelling factual phenomena but operate in a structural chain of relations which makes sense only when different sign configurations are put into practice in everyday life. The following critical commentary emphasizes the pragmatic aspect of meaning generation process besides its semantic aspect and proposes a conceptual framework paving the way for an abductive strategy that iteratively goes in between the analysis of the structural whole and the interpretation of individual meaning units to capture the dynamicity of the sense making process. Standing on this framework, it discusses that combining hermeneutic-interpretive analysis with networkgraph theory based approach would better capture the dynamic and relational nature of sense making than the Principal Components method proposed by the article Field and dynamic nature of sense-making: Theoretical and methodological implications.
Keywords: Culture And Cognition; Meaning Generation; Semiotic Networks; Social Representations